Code for Master's Thesis: Evaluation of Snow Depth Retrievals from ICESat-2 and CryoSat-2 Freeboards Using In-Situ Measurements in the Weddell Sea - Schulze, Kirsten (Zenodo, 2024)
GitHub Repository with Jupyter Notebooks for Evaluation of the KaKo20 Snow Depth Product. This repository contains code developed for my Master's thesis, titled "Evaluation of Snow Depth Retrievals from Differences in ICESat-2 and CryoSat-2 Freeboards Using In-Situ Measurements in the Weddell Sea." The study focuses on evaluating snow depth retrievals using lidar data from ICESat-2 and radar data from CryoSat-2. This satellite-based snow depth product is compared with in-situ snow accumulation data collected by drifting Snow Buoys in the Weddell Sea. The statistical analysis, primarily conducted using Python, focuses on differences between the satellite snow product and snow depth from a simple 1-D thermodynamic model driven by snow accumulation rates from the Snow Buoys. Additionally, auxiliary datasets such as multiyear ice concentration and sea ice concentration are used for intercomparisons to ensure consistency.